Cover Feature: Microfluidic System with Extended‐Gate‐Type Organic Transistor for Real‐Time Glucose Monitoring (ChemElectroChem 6/2020). Issue 6 (27th February 2020) - Didier, Pierre; Lobato‐Dauzier, Nicolas; Clément, Nicolas; Genot, Anthony J.; Sasaki, Yui; Leclerc, Éric; Minamiki, Tsukuru; Sakai, Yasuyuki; Fujii, Teruo; Minami, Tsuyoshi
Abstract : The Cover Feature illustrates that the organic field‐effect transistor (OFET) on her left hand enables read‐out of the glucose recognition information through the connected extended‐gate electrode (i.e. the guitar pick). The fabricated microfluidic system (i.e. the Japanese traditional guitar) performs real‐time glucose monitoring in water. More information can be found in the Communication by P. Didier et al. on page 1332 in Issue 6, 2020 (DOI: 10.1002/celc.201902013 ).